Oriented clonal cell dynamics enables accurate growth and shaping of vertebrate cartilage - Kaucka, Marketa; Zikmund, Tomas; Tesarova, Marketa; Gyllborg, Daniel; Hellander, Andreas; Jaros, Josef; Kaiser, Jozef; Petersen, Julian; Szarowska, Bara; Newton, Phillip T; Dyachuk, Vyacheslav; Li, Lei; et al. (eLife, 2017)
Cartilaginous structures are at the core of embryo growth and shaping before the bone forms. Here we report a novel principle of vertebrate cartilage growth that is based on introducing transversally-oriented clones into pre-existing cartilage. This mechanism of growth uncouples the lateral expansion of curved cartilaginous sheets from the control of cartilage thickness, a process which might be the evolutionary mechanism underlying adaptations of facial shape. In rod-shaped cartilage structures (Meckel, ribs and skeletal elements in developing limbs), the transverse integration of clonal columns determines the well-defined diameter and resulting rod-like morphology. We were able to alter cartilage shape by experimentally manipulating clonal geometries. Using in silico modeling, we discovered that anisotropic proliferation might explain cartilage bending and groove formation at the macro-scale.
Keywords: developmental biology; mouse mutants; mouse; Computer Simulation; facial cartilage growth; počítačová simulace; Mice; scaling and shaping; Cartilage; Models, Biological; obratlovci; BMP; GSalpha; zvířata; Wnt/PCP; Vertebrates; mathematical and material modelling; chrupavka; biologické modely; myši; chondrocranium; stem cells; Animals